Designing Mitigation of Failure for Invoice Payment Process at Electric Energy Provider - R, Widyasari; Arvitrida, Niniet Indah (Riviera Publishing, 2025)
Vendor invoice payment process at PT XYZ involves several verification stages supported by a digitalized system through the Vendor Invoicing Portal (VIP) application. Although technology has streamlined workflows, the document rejection rate remains relatively high, averaging 22% between January and August 2024. This equates to 13,435 rejected invoices out of 61,852 processed, with a total value of approximately IDR 5.3 trillion. These rejections are caused by document discrepancies, incomplete submissions, and prolonged correction times by the relevant units or vendors. As a result, payment delays have led to IDR 531.1 billion worth of invoices being paid more than 20 days after submission, negatively impacting the company's operational efficiency and vendor relationships. This study aims to identify business process activities in invoice payments, analyse the risk factors (risk agents) and risk events, and design mitigation strategies to minimize their impact. Analytic Network Process (ANP) method, used to determine the weight of correlation between risks, while the House of Risk (HOR) method identifies priority risks based on the Aggregate Risk Potential (ARP) value. Findings of this study are expected to provide relevant risk mitigation recommendations to reduce the document rejection rate and expedite payment processes. By addressing these issues, the company can enhance operational efficiency and strengthen vendor trust, ensuring that invoices amounting to billions of rupiah are processed more accurately and promptly.